EXTENDING GAMING DEMAND: SUBJECTIVE EXPERIENCES OF COGNITIVE, EMOTIONAL, PHYSICAL, AND SOCIAL VIDEOGAMING REQUIREMENTS - Bowman, Nicholas David; Banks, Jaime (AoIR Selected Papers of Internet Research, 2020)
Videogames directly involve players as co-creators of on-screen events, and this interactivity is assumed to be a core source of their attraction as a successful entertainment medium. Although interactivity is an inherent property of the videogame, it is variably perceived by the end user—for some users, perceived as a more demanding process, taxing their already-limited attentional resources. At least four such demands have been explicated in extant literature: cognitive (making sense of game logics/tasks), emotional (affective responses to game events/outcomes), physical (managing controller inputs and interfaces), and social (responding to human/nonhuman in-game others). Past work has reported empirical support of these concepts through validation of closed-ended survey metrics (e.g., Video Game Demand Scale). The current study challenges and extends the demand concept through an analysis of players’ own language when describing videogame demands in short essays about gaming experiences—critical given that people may experience a phenomenon in ways not accounted for in deductive data approaches. A secondary analysis of qualitative data made freely available by VGDS authors revealed both convergence with and divergence from prior work. Comporting with VGDS, cognitive demands are mostly experienced by players as ludic concerns and physical demands are mostly experienced in relation to handheld controller perceptions. Diverging from VGDS, players’ emotional demands represented both basic and complex emotional states, and social demands manifest different depending on whether or not the social “other” is human or non-human: humans are considered demanding on interpersonal terms, whereas non-humans are considered demanding as personified evocative objects.